Three New Steroidal Glycosides from the Roots of Cynanchum stauntonii - Yu, Jin-Qian (Hindawi Publishing Corporation, 2013)

(untitled)
Three new steroidal glycosides, named as stauntosides L, M, and N (1–3), along with one known C(21) steroidal glycoside, anhydrohirundigenin monothevetoside (4), were isolated from the 95% ethanol extract of the roots of Cynanchum stauntonii. The structures of these new compounds were elucidated on the basis of extensive spectroscopic analyses, mainly 1D and 2D NMR, HRESI-MS, and chemical methods.